If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1)(x + 2) = x(x + -5) Reorder the terms: (-1 + x)(x + 2) = x(x + -5) Reorder the terms: (-1 + x)(2 + x) = x(x + -5) Multiply (-1 + x) * (2 + x) (-1(2 + x) + x(2 + x)) = x(x + -5) ((2 * -1 + x * -1) + x(2 + x)) = x(x + -5) ((-2 + -1x) + x(2 + x)) = x(x + -5) (-2 + -1x + (2 * x + x * x)) = x(x + -5) (-2 + -1x + (2x + x2)) = x(x + -5) Combine like terms: -1x + 2x = 1x (-2 + 1x + x2) = x(x + -5) Reorder the terms: -2 + 1x + x2 = x(-5 + x) -2 + 1x + x2 = (-5 * x + x * x) -2 + 1x + x2 = (-5x + x2) Add '-1x2' to each side of the equation. -2 + 1x + x2 + -1x2 = -5x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -2 + 1x + 0 = -5x + x2 + -1x2 -2 + 1x = -5x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -2 + 1x = -5x + 0 -2 + 1x = -5x Solving -2 + 1x = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -2 + 1x + 5x = -5x + 5x Combine like terms: 1x + 5x = 6x -2 + 6x = -5x + 5x Combine like terms: -5x + 5x = 0 -2 + 6x = 0 Add '2' to each side of the equation. -2 + 2 + 6x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 6x = 0 + 2 6x = 0 + 2 Combine like terms: 0 + 2 = 2 6x = 2 Divide each side by '6'. x = 0.3333333333 Simplifying x = 0.3333333333
| (4X3y5/2x4y2)3 | | 7=1/2x | | 856=4m | | 48=14u-8u | | -19x-12=-50 | | 4(3y-5)-(6y+5)= | | -4(5t-4)+6t=7t-6 | | -19x-12=50 | | -40=w-9 | | 10x-3x=63 | | x(x-2)=(x+1)(x-3) | | (n-1/(4n-6))-1/4 | | -17x-15=-100 | | (n-1/4n-6)-1/4 | | 2y^2-6y=16 | | 2.3+y=1.6 | | 7+18+3x=34 | | 9x^2=18x-27 | | 6y-13y=14 | | 9x+12=6x+18 | | 4-9/7=3 | | 2v^2+7v-34=-2 | | 5x+52=4x+40 | | 6x+52=4x+40 | | 9x+11=7x+3x+5 | | 4*cos*4x=0 | | (r+8)(-2)=12 | | -5x+17y=-23 | | z=pq+4px+qy | | 2x-14y=18 | | Cos4x=1/4 | | -(1-8a)=-31-7a |